TOURISM AND ECONOMIC STRUCTURE IN A SMALL-OPEN GROWTH MODEL - ZHANG, Wei-Bin (Journal of Environmental Management and Tourism; Vol 3 No 2 (2012): JEMT Volume III Issue 2(6) Winter 2012, 2016)
The purpose of this study is to examine effects of tourism on economic development. We build an economic growth model of a small open country with tourism in a perfectly competitive economy. The economy consists of one service sector and one industrial sector. International tourists and domestic residents consume non-traded goods and services. The land is distributed between housing and supply of services. The production side is the same as in the neoclassical growth theory, while we use an alternative utility function to determine behavior of the household. The system has a unique stable equilibrium point. We simulate the motion of the national economy and examine effects of changes in the rate of interest, the price elasticity of tourism, the global economic condition, the total productivities of the industrial and service sectors, and the propensity to save. The comparative dynamic analysis provides some important insights. For instance, when the price elasticity of tourism is increased, the tourist demand and the price of services are reduced; national trade balance is deteriorated; the output of the service sector is reduced and the output of the industrial sector is increased; some of labor force is shifted from the service sector to the industrial sector; the lot size falls and the land input of the service sector is reduced; and the GDP, the consumption levels of the goods and services and wealth level rise initially but fall in the long term.
Keywords: tourism; price elasticity of tourism; growth; capital accumulation; small open economy